Improvement in thermoelectric performance of In6Se7 by substitution of Sn for In. Issue 8 (29th February 2016) - Cheng, Min; Chen, Shaoping; Du, Zhengliang; Liu, Xianglian; Cui, Jiaolin
Abstract : In this work we have observed a remarkable improvement in the thermoelectric (TE) performance of In6– x Sn x Se7 ( ZT  = ∼0.28 at x  = 0.1, 833 K) compared to that of pristine In6 Se7 ( ZT  = 0.015 at 640 K). This improvement is mainly attributed to the creation of active donor defects SnIn 3+ as Sn(4+) is energetically favorable to In + sites. Although Sn (2+), which generates a defect SnIn − as an acceptor when it is incorporated into the In 3+ sites, has a negative effect on the transport properties, the counter effect from Sn(4+) and Sn(2+) suggests that In6 Se7 ‐based alloys are prospectively good thermoelectric candidates if their chemical compositions are well optimized.